Oxidative-Stress-Related Genes in Osteoporosis: A Systematic Review - Guadalupe León-Reyes; Anna D. Argoty-Pantoja; Adriana Becerra-Cervera; Priscilla López-Montoya; Berenice Rivera-Paredez; Rafael Velázquez-Cruz (MDPI AG, 2023)
Osteoporosis is characterized by a decline in bone mineral density (BMD) and increased fracture risk. Free radicals and antioxidant systems play a central role in bone remodeling. This study was conducted to illustrate the role of oxidative-stress-related genes in BMD and osteoporosis. A systematic review was performed following the PRISMA guidelines. The search was computed in PubMed, Web of Sciences, Scopus, EBSCO, and BVS from inception to November 1st, 2022. The risk of bias was evaluated using the Joanna Briggs Institute Critical Appraisal Checklist tool. A total of 427 potentially eligible articles exploring this search question were detected. After removing duplicates (n = 112) and excluding irrelevant manuscripts based on screenings of their titles and abstracts (n = 317), 19 articles were selected for full-text review. Finally, 14 original articles were included in this systematic review after we applied the exclusion and inclusion criteria. Data analyzed in this systematic review indicated that oxidative-stress-related genetic polymorphisms are associated with BMD at different skeletal sites in diverse populations, influencing the risk of osteoporosis or osteoporotic fracture. However, it is necessary to look deep into their association with bone metabolism to determine if the findings can be translated into the clinical management of osteoporosis and its progression.